Arrival stories : women share their experiences of becoming mothers - Schumer, Amy; Turlington, Christy, 1969-; Williams, Serena, 1981-; Montaño, Alysia; Lopez, Abby G.; Tamblyn, Amber; Tamblyn, Amber; Shah, Shilpa; Burns, Christy Turlington; Oster, Emily; Hansen, Emma, 1990-; Feist; et al. (The Dial Press, 2022)
"Two pink lines on a pregnancy test. The primal scream of a woman pushing through her thirty-fifth hour of labor. The moment a still-wet newborn is placed in his mother's open arms after an unexpected c-section. The bottomless love reflected in the eyes of a father seeing his daughter for the first time. The moment a baby latches to her mother's breast. Or the moment that mother decides to switch to formula. Each of these, and so many more, are stories of entering motherhood. Motherhood is an identity, a calling, a battle, a journey. By sharing their experiences, the contributors to Arrival Stories offer an informative and deeply affecting account of what it feels like when a woman first realizes she is a mother. Throughout her difficult pregnancy, and following her frightening labor experience, Amy Schumer found camaraderie and empowerment in hearing birth stories from other women, including that of her friend, activist Christy Turlington Burns. It is through their conversations that the idea for this book was born. Intimate and urgent, Arrival Stories offers a panoramic view of motherhood, and highlights the grave injustices that women of color face in maternal healthcare. It is the perfect book for any expectant or new mother, or for anyone who knows and loves one"--